2005
DOI: 10.1111/j.1742-4658.2005.04692.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium modulates endopeptidase 24.15 (EC 3.4.24.15) membrane association, secondary structure and substrate specificity

Abstract: The metalloendopeptidase 24.15 (EP24.15) is ubiquitously present in the extracellular environment as a secreted protein. Outside the cell, this enzyme degrades several neuropeptides containing from 5 to 17 amino acids (e.g. gonadotropin releasing hormone, bradykinin, opioids and neurotensin). The constitutive secretion of EP24.15 from glioma C6 cells was demonstrated to be stimulated linearly by reduced concentrations of extracellular calcium. In the present report we demonstrate that extracellular calcium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
(78 reference statements)
2
12
0
Order By: Relevance
“…2A, lanes 2 and 3) and secreted ( Fig. 2A, lanes 5 and 6), consistent with previous reports by other investigators Oliveira et al, 2005). Some cell-associated specific HA-EP species of lower molecular masses (60 -70 kDa) were also detected ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…2A, lanes 2 and 3) and secreted ( Fig. 2A, lanes 5 and 6), consistent with previous reports by other investigators Oliveira et al, 2005). Some cell-associated specific HA-EP species of lower molecular masses (60 -70 kDa) were also detected ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, epitopetagged EP24.15 was clearly visible, and it was found to be widely distributed in the cells with cytosolic, particulate, and secreted forms of the enzyme, which is consistent with previous observations of endogenous EP24.15 in other cells with higher endogenous enzyme expression (Crack et al, 1999;Ferro et al, 1999;Jeske et al, 2004;Oliveira et al, 2005). The particulate form of EP24.15 was localized both on the extracellular face of the plasma membrane and in endocytic vesicles, whereas no colocalization with either the ER marker calnexin or the Golgi marker GM130 was observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although many immunologically-based studies have demonstrated EP24.15 expression on the plasma membrane, there exists some ambiguity as to the inside-outside orientation of the peptidase from a functional standpoint [7,11,1416,27,30,31]. To investigate this, we treated TG cultures with diluted trypsin, and measured EP24.15 and EP24.16 activity in cytoplasmic and plasma membrane fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using peptide agonists, at least in the case of opioid receptors, have shown that the co-endocytosed agonist is recycled back to the surface or processed in an acidic compartment, depending on the length of agonist treatment (17,53). Relatively few studies have focused on the enzymes that are responsible for post-endocytic peptide agonist degradation, although a number of peptidases have been shown to be capable of hydrolyzing neuroendocrine peptides including opioid peptides (2,45,54,55). Among them, an enzyme named enkephalinase (EC 3.4.24.11), originally thought to be solely responsible for enkephalin degradation, was soon shown to be able to degrade a number of other neuropeptides, and because it exhibited activity at neutral pH it was renamed "neutral endopeptidase" or neprilysin (6,8,56).…”
Section: Discussionmentioning
confidence: 99%